Crédito rural e meio ambiente: análise do financiamento pecuário, aplicações e limites de instrumentos para a preservação ambiental - Ribeiro, Amanda Vasconcelos (Universidade Federal de São Carlos, 2024)
Rural credit and environmental preservation are directly linked topics when it comes to financial institutions and the availability of credit subsidies. Through research with data from recent harvest years, where it is possible to compare the amount of financing that was made available and the increase in deforestation in different regions of the country, we will be able to discuss the correlation between the two factors, therefore, we will have an analysis of whether they are directly linked or not, taking into account aspects such as sustainability, responsibility and environmental preservation, in addition to proposing better conditions for monitoring the areas used by rural producers and more effective inspection methodologies through the credit providers themselves.
Rural credit and environment: analysis of livestock financing, applications and limits of instruments for environmental preservation
Keywords: Agronegócio; Revolução Verde; Preservação ambiental; Desmatamentos; Pecuária; Agrobusiness; Rural credit; Green revolution; Environmental; Preservation; Deforestation; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS